Bahasa dan Penemuan Hukum Analisis Makna pada Pasal-Pasal dalam KUHP - Frans Sayogie (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2007)
This research aims at analysing the meaning of articles of PenalCode Book. The research findings state that some of the articles of Penal Code Book are re quired to be interpreted in order to gain the clear meaning.